Biodegradable porous polymeric drug as a drug delivery system: alleviation of doxorubicin-induced cardiotoxicity via passive targeted release. Issue 8 (13th February 2023) - Jiao, Qiuhong; Liu, Baoting; Xu, Xiufeng; Huang, Tao; Cao, Bufan; Wang, Lide; Wang, Qingguo; Du, Ailing; Li, Jingtian; Zhou, Baolong; Wang, Tao
Abstract : Alleviation of doxorubicin-induced cardiotoxicity by a biodegradable porous organic polymer drug delivery system via passive targeted release. Abstract : Doxorubicin (DOX) is an effective chemotherapeutic drug developed against a broad range of cancers, and its clinical applications are greatly restricted by the side effects of severe cardiotoxicity during tumour treatment. Herein, the DOX-loaded biodegradable porous polymeric drug, namely, Fc-Ma-DOX, which was stable in the circulation, but easy to compose in the acidic medium, was used as the drug delivery system avoiding the indiscriminate release of DOX. Fc-Ma was constructed via the copolymerization of 1, 1′-ferrocenecarbaldehyde with d -mannitol (Ma) through the pH-sensitive acetal bonds. Echocardiography, biochemical parameters, pathological examination, and western blot results showed that DOX treatment caused increased myocardial injury and oxidative stress damage. In contrast, treatment with Fc-Ma-DOX significantly reduced myocardial injury and oxidative stress by DOX treatment. Notably, in the Fc-Ma-DOX treatment group, we observed a significant decrease in the uptake of DOX by H9C2 cells and a significant decrease in reactive oxygen species (ROS) production.